PENGARUH JUMLAH DAN FREKUENSI ASUPAN CAIRAN TERHADAP OSMOLALITAS URIN SERTA HUBUNGANNYA DENGAN KINERJA KOGNITIF - Angieda Soeparto; Sri Lestari Sulistyo Rini; Ratna Dewi Puspita (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2026)
ABSTRACTBackground: Water play a vital role in physiological functions, including fluid balance and cognitive performance. Mild dehydration can impair cognitive function; however, evidence regarding the impact of volume and frequency fluid intake on hydration status and cognitive performance remains limited, particularly in non-athletic populations.Objectives: To explore the effect of volume and frequency fluid intake on urinary osmolality and its correlation with cognitive performance.Methods: Quasi-experimental study involved three measurements (baseline, pre-test, post-test). Total of 32 participants were divided into four groups: control (CO, n=8), intervention 1 (IN1, 1 L of water consumed within 15 minutes, n=8), intervention 2 (IN2, 250 mL every 30 minutes, 4 times, n=8), and intervention 3 (IN3, 500 mL every 30 minutes, 2 times, n=8). After 12-hour fluid fasting period, urinary osmolality and cognitive performance (Trail Making Test [TMT], Digit Symbol Substitution Test [DSST], and Stroop Test) were measured pre- and post-intervention.Results: IN1 showed the most significant reduction in urinary osmolality (p=0.000). IN3 yielded the best cognitive performance outcomes, with reductions in completion times for TMT-A (p=0.012) and TMT-B (p=0.025), increased DSST scores (p=0.001), and shorter Stroop Test times (p=0.021). A strong positive correlation was found between urinary osmolality and Stroop Test completion time in the IN1 group (p=0.020).Conclusion: A large volume of water consumed at once is effective in reducing urinary osmolality. The combination of fluid intake volume and frequency plays an important role in supporting cognitive performance.Keywords: hydration status; fluid intake behavior; cognitive performance; urinary osmolality. ABSTRAKLatar belakang: Air berperan penting dalam fungsi fisiologis tubuh, termasuk menjaga keseimbangan cairan dan fungsi kognitif. Dehidrasi ringan dapat menurunkan performa kognitif, namun bukti mengenai pengaruh jumlah dan frekuensi asupan cairan terhadap status hidrasi dan fungsi kognitif masih terbatas, terutama pada populasi non-atletik.Tujuan: mengeksplorasi pengaruh jumlah dan frekuensi asupan cairan terhadap osmolalitas urin dan korelasinya dengan kinerja kognitif.Metode: Penelitian menggunakan desain quasi-experimental dengan tiga kali pengukuran (baseline, pre-test, post-test). Sebanyak 32 subjek dibagi menjadi empat kelompok: kontrol (KO, n=8), intervensi 1 (IN1, 1 L air mineral dalam 15 menit, n=8), intervensi 2 (IN2, 250 mL tiap 30 menit sebanyak 4x, n=8), dan intervensi 3 (IN3, 500 mL tiap 30 menit sebanyak 2x, n=8). Setelah puasa cairan 12 jam, dilakukan pengukuran osmolalitas urin dan kinerja kognitif (Trail Making Test, Digit Symbol Substitution Test, Stroop Test) pre dan post intervensi.Hasil: IN1 menunjukkan penurunan osmolalitas urin paling signifikan (p=0,000). IN3 memberikan hasil terbaik pada kinerja kognitif dengan penurunan waktu pengerjaan TMT A (p=0,012) dan TMT B (p=0,025), peningkatan skor DSST (p=0,001), serta penurunan waktu Stroop Test (p=0,021). Terdapat korelasi positif kuat antara osmolalitas urin dan waktu Stroop Test pada IN1 (p=0,020).Simpulan: Volume cairan yang besar dalam satu waktu efektif menurunkan osmolalitas urin. Kombinasi jumlah dan frekuensi asupan cairan berperan penting dalam mendukung fungsi kognitif.Kata Kunci: status hidrasi; perilaku asupan cairan; kinerja kognitif; osmolalitas urin.